Combined Modality Approaches in the Management of Adult Glioblastoma - Shirazi, Haider A.; Grimm, Sean; Raizer, Jeffrey; Mehta, Minesh P. (Frontiers in Oncology, 2011)
Over the past two decades, management of newly diagnosed glioblastoma has undergone significant evolution. While surgery has long been a mainstay of management for this disease, and while radiotherapy has a proven survival role, initial efforts at radiotherapy dose escalation, use of radiosurgery, brachytherapy, and altered fractionation did not improve patient survival. Recently, multiple modality therapy integrating maximal safe resection, postoperative radiation, and new systemic therapies have resulted in improved patient outcomes compared with older regimens utilizing surgery and postoperative radiation alone. Numerous trials are currently underway investigating the combination of surgery, radiation, and systemic therapy with targeted agents to find ways to further improve outcomes for adults with glioblastoma.